FORMULATION OF MICROEMULSION BASED GEL OF SALBUTAMOL SULPHATE AND IT’S IN VITRO STUDIES - JAMIL, LARAIB; JAN, SYED UMER; GUL, RAHMAM (International Journal of Current Pharmaceutical Research, 2020)
Objective: The aim of this study was to develop a microemulsion based gel system considering transdermal delivery of Salbutamol with a purpose to increase the solubility and membrane drug deliverance. Methods: Oleic acid was favored for oil phase owing to the proficiency of solubility in this study. Despite surfactant and co-surfactant was determined by virtue of their solubilizing strength wherewith they developed MEs. Accomplishing Franz diffusion cells equipped with cellulose membrane for in vitro study. The Polymer carbopol 934 were used for based gel preparation to enhance the viscosity of microemulsion for transdermal utilization. The advanced micro emulsion-based gel, which was assessed for pH, centrifugation, spreadability conductivity, drug content, viscosity, SEM, XRD and stability studies. Results: The process of drug escape from microemulsion gel-based was noticed to pursue Korsmeyer-peppas model kinetics. The designed, microemulsion gel-based displayed acceptable stability layer than 3 mo. Drug release microemulsion within 24 h was observed 74%. Conclusion: The results illustrate that deliberated effort to establish microemulsion based gel (F3) was likely to produce sustained action of drug release (78.3%) and be permitted auspicious vehicle for transdermal distribution of Salbutamol.